MEMPELAJARI BAGIAN TANAMAN DAN KONSENTRASI EKSTRAK KUNCI PEPET (Kaempferia rotunda L) YANG MEMPUNYAI SIFAT REPELAN NYAMUK Aedes aegypti - Admadi H, Bambang (Agrotekno; Vol. 15, No. 2 Agustus 2009, 2012)
The research purpose were to find out the part of plantextract and an extract concentration of Narrow-leaf peacockginger as repellant agent to Aedes aegypti mosquito.The research method used the completed randomizeddesign with two factors in factorial experimental. The bothfactors were 1) the plant part to enclose a stalk-root andtuber; 2) an extract concentration with 5 levels to enclose 0,5, 10, 15, 20% so that there were 10 combination treatmentsthat to be replicated 5 times.The results of the research showed that the tuber andstalk-root extracts of Narrow-leaf peacock ginger had anatural repellant constituent. Narrow-leaf peacock gingertuber extract in 15 and 20% concentration had the highest ofrepellant capacity or to kill mosquito. The longer applicationof the extract decreased the repellant capacity, especially thatto be extracted of the stalk-root and tuber in consentrationapplication of 5 and 10%.
Keywords: plant part of narrow-leaf peacock ginger, extract concentration of narrow-leaf peacock ginger, repellant capacity, Aedes aegypti mosquito